Enabling High‐Stability of Aqueous‐Processed Nickel‐Rich Positive Electrodes in Lithium Metal Batteries. Issue 42 (18th September 2022) - Wu, Fanglin; Kuenzel, Matthias; Diemant, Thomas; Mullaliu, Angelo; Fang, Shan; Kim, Jae‐Kwang; Kim, Hee Woong; Kim, Guk‐Tae; Passerini, Stefano
Abstract: Lithium batteries occupy the large‐scale electric mobility market raising concerns about the environmental impact of cell production, especially regarding the use of poly(vinylidene difluoride) (teratogenic) and N ‐methyl‐2‐pyrrolidone (NMP, harmful). To avoid their use, an aqueous electrode processing route is utilized in which a water‐soluble hybrid acrylic‐fluoropolymer together with sodium carboxymethyl cellulose is used as binder, and a thin phosphate coating layer is in situ formed on the surface of the nickel‐rich cathode during electrode processing. The resulting electrodes achieve a comparable performance to that of NMP‐based electrodes in conventional organic carbonate‐based electrolyte (LP30). Subsequently, an ionic liquid electrolyte (ILE) is employed to replace the organic electrolyte, building stable electrode/electrolyte interphases on the surface of the nickel‐rich positive electrode (cathode) and metallic lithium negative electrode (anode). In such ILE, the aqueously processed electrodes achieve high cycling stability with a capacity retention of 91% after 1000 cycles (20 °C). In addition, a high capacity of more than 2.5 mAh cm –2 is achieved for high loading electrodes (≈15 mg cm –2 ) by using a modified ILE with 5% vinylene carbonate additive. A path to achieve environmentally friendly electrode manufacturing while maintaining their outstanding performance and structural integrity is demonstrated. Abstract : Positive electrodes composed of high nickel content active material and aqueous binder offer remarkable cycling stability and high capacity (2.5 mAh cm –2 ) at high loadings in a poorly flammable ionic liquid electrolyte demonstrating a path toward environmentally friendly electrode manufacturing for lithium metal batteries.